Implementasi Pemilihan Pimpinan Karyawan Operasioal Konveksi Pakaian Menggunakan Metode ROC (Rank Order Centroid) dan TOPSIS - Jeperson Hutahaean; Neni Mulyani (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2021)
The selection of employee leaders which is an important process for the company and is the most awaited thing by other employees to improve social status, salaries and many others, it is necessary to select employee leaders to become role models and examples and assist company leaders in managing and monitoring other employees for can work as expected by the leadership of the company, in the selection of company leaders it is necessary to choose a computerized process, namely making a decision support system to get the right and good results based on the system and not based on personal interests, in the decision-making process the ROC and Topsis methods are used as a step procedure that helps get a value with a high level of accuracy, the ROC method is used as a method of finding the weight value of each criterion and will continue the process of finding the highest value using the Topsis method as a ai the chosen alternative. The results obtained were 0.591835 as the highest score and the selected candidates in the selection used the ROC and TOPSIS methods